HORMONAL CONTRACEPTION AND THE RISK OF MENINGIOMA: A NARRATIVE REVIEW OF EVIDENCE FROM PROGESTOGEN-RELATED THERAPIES - Katarzyna Malinowska; Elhatra Settaf-Cherif; Joanna Barwacz; Magdalena Adamik; Layla Settaf-Cherif; Marta Czarnowska; Radosław Sciepuro; Dagmara Gładysz (International Journal of Innovative Technologies in Social Science, 2025)
Background: Meningiomas are the most common benign intracranial tumors in adults and show a marked female predominance, suggesting a hormonal influence. The frequent expression of progesterone and estrogen receptors in these tumors has raised concerns that exogenous hormones, particularly those used in hormonal contraception, may contribute to their development or growth. Aim: To summarize current knowledge about hormonal contraceptive use and the risk of meningioma. Methodology: A narrative review was conducted using PubMed and Google Scholar between January and September 2025. The search included studies related to meningioma, hormonal contraception, and specific progestins such as cyproterone acetate, medroxyprogesterone acetate, nomegestrol acetate, chlormadinone acetate, desogestrel, and levonorgestrel. Results: Most studies do not demonstrate a consistent association between combined estrogen–progestin oral contraceptives and meningioma risk; in contrast, prolonged or high-dose exposure to specific progestin-only agents has been associated with an increased risk. Particularly, depot medroxyprogesterone acetate, cyproterone acetate, nomegestrol acetate, and chlormadinone acetate have been linked to a significantly increased risk, often related to cumulative dose and duration of use. Regression of hormone-associated tumors following treatment withdrawal has been reported, and the excess risk appears to decrease over time after discontinuation. Conclusions: Combined oral contraceptives are generally considered safe, whereas long-term use of potent progestins may promote meningioma growth. Contraceptive choices should be chosen based on individual risk profiles, especially for women requiring extended hormonal therapy. Further studies are needed to clarify underlying mechanisms and identify women at increased susceptibility.